The art of Tangled - Kurtti, Jeff
"A lighthearted twist on Rapunzel, the beloved fairy tale from the Brothers Grimm, Tangled brims with thrilling adventure, a distinctive cast of characters, a daring heroine, and, of course, seventy feet of golden hair. Featuring the stunning concept art behind the newest Disney masterpiece, The Art of Tangled also includes a preface by John Lasseter, a foreword by Directors Nathan Greno and Byron Howard, and interviews with the artists, animators, and production team—including Art Director David Goetz—that shed light on the history and artistry of this landmark film."--